Penerapan Prinsip Transparansi Pada Kegiatan Perdagangan Ditinjau Dari Sifat Amanah Nabi Muhammad - Aprilia; Dwi Gita Nathalia; Rheni Anggraini; Mohamad Djasuli (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
In this modern era, there are many people who trade, both traders and business actors, so that there is more and more competition in trading activities. This makes many people need knowledge and strategies in order to survive in trade competition. This article was written with the aim of disclosing that the actual application of the principle of transparency to trading activities from an Islamic point of view includes applying the trustworthiness of the Prophet Muhammad SAW. This article uses qualitative methods as a research method. The principle of transparency has a relationship with the quality of information presented by business actors. Service quality is very important to note for traders and business actors. With superior service quality, it is able to support the sustainability of its business and survive in tight trade competition. The trustworthy nature of the Prophet Muhammad SAW means being trustworthy in taking care of responsibilities, that's why many people like to transact with him. The secret of the Prophet Muhammad's success in trading was the quality of service and the quality of the trade goods which he paid great attention to.